1996
DOI: 10.1097/00006123-199610000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Neurography of Peripheral Nerve Lesions in the Lower Extremity

Abstract: MRN proved useful in the preoperative evaluation and planning of surgery in patients with peripheral nerve lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…Others have also noted that abnormal peripheral nerves typically demonstrate abnormally high signal on T2-weighted images and that this correlates well with clinical and electrodiagnostic evidence of nerve injury. 9 In contrast, normal nerves are only minimally hyperintense to muscle and show no significant enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have also noted that abnormal peripheral nerves typically demonstrate abnormally high signal on T2-weighted images and that this correlates well with clinical and electrodiagnostic evidence of nerve injury. 9 In contrast, normal nerves are only minimally hyperintense to muscle and show no significant enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,10 MR neurography has been used to detect and evaluate the extent of neural tumors, along with the degree of fascicular distortion caused by these neoplasms. It has been suggested that by distinguishing normal nerve from nerve tumor, and demonstrating the precise relationship of the nerve to the tumor, MR neurography can provide guidance for surgery and intraoperative monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (Prevot et al, 1990;Leitjen et al, 1992;Lang et al, 1994;Dubuisson and Stevenaert, 1996;Aulisa et al, 1998) and CT (Firooznia et al, 1983;Pazzaglia, et al, 1989;Gambari et al, 1990;Antonini et al, 1991) have both been used in an attempt to characterize these cysts and their origins but have fallen short when compared to optimized MRI techniques and the superior soft-tissue contrast and high spatial resolution (Leon and Marano, 1987;Coakley et al, 1995;Kuntz et al, 1996;Uetani et al, 1998;Grant et al, 2004). Even MRI, however, may not be adequate to demonstrate joint connections, if optimized techniques are not used.…”
Section: Discussionmentioning
confidence: 99%
“…When used together with a clinical examination, MR imaging can confirm the presence of a mass and visualize the fine anatomical details of involved peripheral nerves. Magnetic resonance neurography 8,9,15 comprises a series of techniques that further enhance the contrast between peripheral nerves and surrounding tissues. By employing special pulse sequences, high-field strength scanners, and multiple phased-array coils optimized for a particular body region, an improved signal-tonoise ratio can be achieved, leading to a higher spatial resolution and greater contrast while maintaining an adequate FOV (Fig.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%